2017
DOI: 10.1021/acsami.7b06028
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination of Boron-Doped Diamond Film Electrodes for Minimization of Perchlorate Formation

Abstract: This research investigated the effects of surface fluorination on both rates of organic compound oxidation (phenol and terephthalic acid (TA)) and ClO formation at boron-doped diamond (BDD) film anodes at 22 °C. Different fluorination methods (i.e., electrochemical oxidation with perfluorooctanoic acid (PFOA), radio frequency plasma, and silanization) were used to incorporate fluorinated moieties on the BDD surface, which was confirmed by X-ray photoelectron spectroscopy (XPS). The silanization method was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The extent of deviation increases with further increase in overpotential, indicating increased ACSFR activity. The reduced OER (i.e., increased ACSFR) selectivity with increase in potential is further confirmed by DPD colorimetry (Supporting Information section S3; Figure b). The reduced OER and increased ACSFR selectivity with increase in potential are further confirmed by DPD colorimetry, wherein 3, 11, 20, and 32% ACSFR current efficiencies are achieved at 1.70, 1.75, 1.80, and 1.85 V vs RHE, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 62%
“…The extent of deviation increases with further increase in overpotential, indicating increased ACSFR activity. The reduced OER (i.e., increased ACSFR) selectivity with increase in potential is further confirmed by DPD colorimetry (Supporting Information section S3; Figure b). The reduced OER and increased ACSFR selectivity with increase in potential are further confirmed by DPD colorimetry, wherein 3, 11, 20, and 32% ACSFR current efficiencies are achieved at 1.70, 1.75, 1.80, and 1.85 V vs RHE, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 62%
“…Our arguments that hydrophobic molecular layers inhibit inner-sphere reactions are supported by two prior studies. Gayen et al showed that hydrophobic, perfluorinated monolayer on BDD blocked ClO 3 – from reaching the electrode surface, while still allowing for • OH formation . Zhao et al also reported that modification of PbO 2 anodes with hydrophobic fluorine resin increased oxygen evolution overpotential and thereby increased • OH production efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…Gayen et al 43 showed that hydrophobic, perfluorinated monolayer on BDD blocked ClO 3 − from reaching the electrode surface, while still allowing for • OH formation. 43 Zhao et al also reported that modification of PbO 2 anodes with hydrophobic fluorine resin increased oxygen evolution overpotential and thereby increased • OH production efficiency. 17 Taken together, they suggest that the use of hydrophobic layers to inhibit inner-sphere reactions in aqueous media may be a general phenomenon.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations